THE IMPACT OF MATHEMATICS IN SCIENCE AND TECHNOLOGY DEVELOPMENT - Loso Judijanto; Charisal Matsen A Manu; Joni Wilson Sitopu; Navel Oktaviandy Mangelep; Alim Hardiansyah (International Journal of Teaching and Learning, 2024)
Mathematics is a basic science that is very necessary as a foundation for modern technology and knowledge. Apart from that, Mathematics gives a person high skills in terms of abstraction, problem analysis and logical reasoning. In this way, mathematics functions to help study the natural environment so that it can be developed into technology for the welfare of humanity. This research aims to find out the role of mathematics in science and technology. By using the library study method where data is collected and obtained from various sources. The data source uses secondary data obtained from published scientific journal articles. The conclusion of this research is that mathematics has several important roles in science and technological development, namely mathematics as the language of science, mathematics as logic and deductive in science, mathematics as the basis of programming languages, mathematics can express the position of a point, line, plane or object. which is used to create animated videos, and mathematics as a basis for hardware and software development.